Peningkatkan Hasil Belajar Matematika Melalui Pembelajaran Dengan Pendekatan Metakognisi Pada Siswa Kelas VIII C Smpn 2 Polewali - Syamsuddin Syamsuddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2013)
This research is action research ( Classroom Action Research ) which aims to improve mathematics learning outcomes involving metacognition VIIIc grader at SMP 2 Polewali semester of academic year 2010/2011 the number of 34 students . Classroom action research was carried out with 2 cycles , the first cycle comprises 4 meeting and the second cycle consists of 4 meetings . Technique is to use a data collection sheet and the test observation in narrative form at the end of each cycle in accordance with the material being taught . Based on analysis of the data obtained it can be concluded that , qualitatively there are some changes . students showed enthusiasm to attend classes , boldness of expression, response , asking about the material that is not understood to be increased. While quantitatively , an increase in the average score of student learning outcomes VIIIc SMP 2 Polewali is of medium category with an average score of 54.02 after the implementation of the first cycle of action into high category with an average score of 66.17 after the implementation of the Cycle II . From these results it can be concluded that with the implementation of learning that involve metacognition in class 2 Polewali SMP VIIIc in the learning process , the results of studying mathematics , attendance , preparedness and student activity can be increased.